Evaluation of the Effects of Vaccinium arctostaphylos L. Fruit Extract on Serum Lipids and hs-CRP Levels and Oxidative Stress in Adult Patients with Hyperlipidemia: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial. (23rd January 2014) - Soltani, Rasool; Hakimi, Mustafa; Asgary, Sedigheh; Ghanadian, Syed Mustafa; Keshvari, Mahtab; Sarrafzadegan, Nizal
Abstract : Background. Dyslipidemia produces atherosclerosis, which in turn results in coronary artery disease (CAD). Atherosclerosis is being considered as an inflammatory disease. Vaccinium arctostaphylos L. is a plant with fruits rich in anthocyanins. The aim of this study was to evaluate the effects of fruit extract of this plant on serum levels of lipids, hs-CRP, and malondialdehyde (MDA) as a marker of oxidative stress, in hyperlipidemic adult patients. Methods. In this randomized, double-blind, placebo-controlled clinical trial, 50 hyperlipidemic adult patients were randomly and equally assigned to receive either medicinal ( V. arctostaphylos fruit extract) or placebo capsules twice daily for 4 weeks. Each medicinal capsule contained 45 ± 2 mg of anthocyanins. Fasting serum levels of total cholesterol, TG, LDL-C, HDL-C, hs-CRP, and MDA were obtained before and after the intervention and compared. Results. V. arctostaphylos fruit extract significantly reduced total cholesterol (P < 0.001 ), LDL-C (P = 0.004 ), TG (P < 0.001 ), and MDA (P = 0.013 ) compared to placebo but did not have any significant effect on HDL-C (P = 0.631 ) and hs-CRP (P = 0.190 ). Conclusion. Fruit extract of Vaccinium arctostaphylos has beneficial effects on serum lipid profile and oxidative stress in hyperlipidemic adult patients. Therefore, it could be considered as a supplement for treatment of dyslipidemia and prevention of atherosclerosis development.